Seroprevalence study of HCV Genotypes in two tertiary hospital and its association with risk factors and current management practice - Hasmoni, Mohamed Hadzri; Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Amar, Azril Haris Yafee (Malaysian Medical Associations, 2009)
The distribution of hepatitis C virus (HCV) genotypes is well documented in many countries. However, reliable data are still lacking with respect to the frequency of the different HCV genotypes in Malaysia. This study aim to identify HCV genotypes and associated risk factors in a group of HCV infected patients from two tertiary hospitals.